Efektivitas Ekstrak Daun Gambir Sebagai Inhibitor Pada Baja Karbon API 5L dengan Perlakuan Panas Menggunakan Larutan NaCl 3% - Ilwan Pusaka; Ediman Ginting Suka; Yanti Yulianti (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
Abstract.The effectiveness of uncaria gambir leaves extract as inhibitor on carbon steel API 5L with heat treatment in NaCl 3% had been researched. The research was done by weight loss. Corrosion rate had been tested on carbon steel API 5L with heat treatment and carbon steel without heat treatment in NaCl 3% added by soursop leaves extract inhibitor for 168 hours with concentrations of 0%, 2%, 4%, and 6%. The result showed at carbon steel API 5L with and without heat treatment corrosion rate higher at concentration inhibitor 0% that is 0,051 mm/y. While corrosion rate lower at concentration inhibitor 2% that is 0,03%. Until, Efficiency higher at carbon steel API 5L with and without heat treatment in concentration inhibitor 2% that is 61,63% and 66,43%. The X-Ray Diffraction (XRD) characterization result showed at carbon steel API 5L with heat treatment that the phase formed is martensite. At carbon steel API 5L with heat treatment that the phase formed is pure Fe. Scanning Electron Microscopy (SEM) characterization at carbon steel API 5L with heat treatment showed even clusters and larger size, holes, cracks and grain boundary in the surface. At carbon steel API 5L without heat treatment showed uneven clusters and smaller size, holes, cracks, but grain boundary not showed in the surface. Energy Dispersive Spectroscopy (EDS) characterization on sample with inhibitor 0% obtained Cl element and Oxygen larger than inhibitor 2%. Key words:Carbon steel API 5L, soursop leaves extract, corrosion inhibitor, NaCl and heat treatment